Chronic inflammatory pain alters alcohol-regulated frontocortical signaling and associations between alcohol drinking and thermal sensitivity - M. Adrienne McGinn; Kimberly N. Edwards; Scott Edwards (Neurobiology of Pain, 2020)
Alcohol use disorder (AUD) is a chronic, relapsing psychiatric disorder that is characterized by the emergence of negative affective states. The transition from recreational, limited intake to uncontrolled, escalated intake is proposed to involve a transition from positive to negative reinforcement mechanisms for seeking alcohol. Past work has identified the emergence of significant hyperalgesia/allodynia in alcohol-dependent animals, which may serve as a key negative reinforcement mechanism. Chronic pain has been associated with enhanced extracellular signal-regulated kinase (ERK) activity in cortical and subcortical nociceptive areas. Additionally, both pain and AUD have been associated with increased activity of the glucocorticoid receptor (GR), a key mediator of stress responsiveness. The objectives of the current study were to first determine relationships between thermal nociceptive sensitivity and alcohol drinking in male Wistar rats. While inflammatory pain induced by complete Freund’s adjuvant (CFA) administration did not modify escalation of home cage drinking in animals over four weeks, the relationship between drinking levels and hyperalgesia symptoms reversed between acute (1 week) and chronic (3–4 week) periods post-CFA administration, suggesting that either the motivational or analgesic effects of alcohol may be altered over the time course of chronic pain. We next examined ERK and GR phosphorylation in pain-related brain areas (including the central amygdala and prefrontal cortex subregions) in animals experiencing acute withdrawal from binge alcohol administration (2 g/kg, 6 h withdrawal) and CFA administration (four weeks) to model the neurobiological consequences of binge alcohol exposure in the context of pain. We observed a significant interaction between alcohol and pain state, whereby alcohol withdrawal increased ERK phosphorylation across all four frontocortical areas examined, although this effect was absent in animals experiencing chronic inflammatory pain. Alcohol withdrawal also increased GR phosphorylation across all four frontocortical areas, but these changes were not altered by CFA. Interestingly, we observed significant inter-brain regional correlations in GR phosphorylation between the insula and other regions investigated only in animals exposed to both alcohol and CFA, suggesting coordinated activity in insula circuitry and glucocorticoid signaling in this context. The results of these studies provide a greater understanding of the neurobiology of AUD and will contribute to the development of effective treatment strategies for comorbid AUD and pain.